Effects of MARDI nano-fertilizer application frequency on the growth of rock melon - Fadzil, Nadia Izati; Masdor, Noor Azlina; Mohd Rosmi, Mohd Nor; Wahid, Nur Sabrina; Mohd Nor, Nor Suzaida; Abd. Karim, Muhamad Shafiq; Mohd Anuar, Mohd Firdaus (Universiti Malaysia Perlis, 2024)
For many years, fertilizers have been utilized in agriculture to increase the fruit yield and quality of various crops, which in turn will increase the nutritive content of products. Recently, MARDI has developed a nano-fertilizer based on nanoemulsions to increase the productivity of rock melon. The development of nanoemulsion-based fertilizer was carried out using the high-energy emulsification method which has significant advantages, such as enhancing the solubilization of active constituents while preserving biological activity. In this work, the effects of the vegetative growth of rock melon on different application frequencies (T1=0, T2=2, T3=4, T4=6, and T5=8 times) of MARDI nano-fertilizer through foliar treatment were studied. The results showed that the vegetative growth of the rock melon including plant height, stem diameter, relative chlorophyll content, and leaf area of rock melon were significantly (p≤0.05) increased by 15.07%, 7.8%, 41.5% and 41.5%, respectively at T3, photosynthetic pigments of Chlorophyll a by 21.1% at T5, Chlorophyll b and carotenoid by 24.99% at T4 treatment. The dry weight biomass did not vary significantly in all treatments but showed an increase in dry biomass over the nano-fertilizers treatment compared to the control. These findings indicate that adding the foliar application of MARDI nano-fertilizer produces optimal growth in rock melon plants.